Pengelolaan Surat Masuk dan Keluar pada Bagian Tata Usaha Badan Pertanahan Nasional Kota Medan - Sri Mutia Fazira; Nursantri Yanti (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
Management of incoming and outgoing mail has an important role in the efficiency and effectiveness of the administration of the Medan City National Land Agency (BPN). This research aims to analyze the process of managing incoming and outgoing mail and identify the challenges faced in this process. Data collection methods were carried out through direct observation, interviews and documentation studies. The research results show that the management of incoming and outgoing mail at BPN Medan City has improved through the implementation of a mail management information system. However, there ar e still several obstacles such as the length of time the process of entering letters is made and letters being lost. This research recommends improving procedures, increasing internal coordination, and investing in information technology infrastructure to increase the efficiency and effectiveness of managing incoming and outgoing mail at BPN Medan City.